STORYWEAVER’S INTEGRATED CIRC LEARNING MODEL: AN INNOVATIVE SOLUTION TO IMPROVING READING COMPREHENSION SKILLS IN ELEMENTARY SCHOOLS - Nur Latifah; Rissa Alivia Zahra (Universitas Islam Negeri Mataram, 2025)
Low reading comprehension among elementary students remains a significant educational challenge in Indonesia, often stemming from passive instructional methods and low student engagement levels. At SDN Sukatani 5, many students faced difficulties in reading fluently and understanding texts, mainly due to teacher-centered and individual-based classroom practices. This situation underscores the urgent need for more engaging, student-centered learning strategies to enhance literacy skills. This study investigates the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model, which is supported by the StoryWeaver digital platform, in enhancing reading comprehension. Adopting a quantitative experimental design, the research involved 60 fourth-grade students, divided into two cohorts. The experimental cohort received the CIRC-StoryWeaver intervention, while the control cohort was taught utilizing traditional methods. Pre- and post-tests were administered, and data were analyzed using descriptive statistics, t-tests, and N-Gain scores. The outcomes revealed a significant improvement in the experimental cohort, by a post-test average score of 84.07 and an N-Gain of 60.97% (moderate effect), compared to the control cohort’s score of 79.70 and N-Gain of 49.07% (lower effect). These findings reinforce the relevance of constructivist approaches in literacy instruction and demonstrate the potential of digital tools, such as StoryWeaver, to support active, meaningful, and student-centered learning experiences.